Healthcare for older people in lower and middle income countries - Tan, Maw Pin * (Oxford University Press, 2022)
Two-thirds of the world’s population aged 60 years and over will reside in lower and middle income countries (LMIC) by 2050. Many LMICs are experiencing rapid population ageing at a faster rate than in Western Europe and North America, but may not have the resources to respond to the World Health Organization’s call to action. As population ageing is a global issue, effective and sustainable global solutions are much needed. Proposed strategies include stemming the outflow of trained healthcare workers to high-income nations where migrants from LMICs often contribute to the work force caring for older people. Public education, preventive measures and innovative approaches to training are additional proposed solutions. Higher income countries have a responsibility to contribute towards the development of healthcare services for older people in LMICs.